Automated Food Preserving System Utilizing NodeMCU ESP8266-Based Drying Methodology - Marpaung, Maikel; Susilawati (Universitas Medan Area, 2025)
Food drying is one of the effective methods for preserving food and extending its shelf life by inhibiting bacterial growth. In Indonesia, many food products require sun drying to preserve them. However, this process often disrupts due to sudden rain showers, which can impede the drying process. Therefore, a automatic food cover system is needed to facilitate human work and protect the drying process from rain disturbances. This study designs an apparatus that can automatically cover dried food using FC-37 rain sensor controlled by NodeMCU ESP8266. The device also features an email notification feature to provide information on whether it's raining or not, allowing users to take action before the rain arrives. With this automatic food cover system, we expect to improve efficiency and quality of food drying results.